2022
DOI: 10.1038/s41419-022-05110-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated modification of MUC1 maybe a new target to promote drug sensitivity and efficacy for breast cancer chemotherapy

Abstract: Breast cancer, the most common cancer in women, usually exhibits intrinsic insensitivity to drugs, even without drug resistance. MUC1 is a highly glycosylated transmembrane protein, overexpressed in breast cancer, contributing to tumorigenesis and worse prognosis. However, the molecular mechanism between MUC1 and drug sensitivity still remains unclear. Here, natural flavonoid apigenin was used as objective due to the antitumor activity and wide availability. MUC1 knockout (KO) markedly sensitized breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…MUC1 glycosylation modifications also regulate the chemosensitivity of breast cancer cells, with Xi et al. confirming that knocking out MUC1 or removing specific glycosylation modifications enhances chemotherapy effects ( 50 ). In triple-negative breast cancer (TNBC) research, Yamashita et al.…”
Section: The Relevance Of Muc1 and Muc16 To Tumor Development And Pro...mentioning
confidence: 98%
“…MUC1 glycosylation modifications also regulate the chemosensitivity of breast cancer cells, with Xi et al. confirming that knocking out MUC1 or removing specific glycosylation modifications enhances chemotherapy effects ( 50 ). In triple-negative breast cancer (TNBC) research, Yamashita et al.…”
Section: The Relevance Of Muc1 and Muc16 To Tumor Development And Pro...mentioning
confidence: 98%
“…MUC1 is overexpressed in various solid tumors, particularly BC, and has become the most relevant and important antigen in BC-targeted therapy. Studies have shown that the targeted O-GalNAc modification of MUC1 plays a role in changing the chemotherapy tolerance of BC and improving the efficacy of anti-tumor therapy 20 . Mucin antigen vaccines are being actively used to treat various solid tumors.…”
Section: O-glycosylation and Immunotherapymentioning
confidence: 99%
“…The glycosylation of proteins, especially cell surface proteins, plays a significant part in the development of many diseases [1–7] . For example, it has been shown in recent years that the glycosylation‐related processes of surface proteins are significantly altered in cancer cells, [4,8] which is closely related to the growth [9] and metastasis [10] of tumors and their capacity for immunosuppression [11–12] and drug resistance [13–14] . This abnormality provides a handle for selective targeting of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For example, it has been shown in recent years that the glycosylation-related processes of surface proteins are significantly altered in cancer cells, [4,8] which is closely related to the growth [9] and metastasis [10] of tumors and their capacity for immunosuppression [11][12] and drug resistance. [13][14] This abnormality provides a handle for selective targeting of cancer cells. Moreover, this anomaly also offers an entry point for the development of a noninvasive approach to visualize real-time glycosylation fluctuations of surface proteins in cancer cells, which is critical for deepening our understanding on the role of glycosylation in tumor progression.…”
Section: Introductionmentioning
confidence: 99%